44.8k views
0 votes
Simplify (2/3 + 1/6)

User Sloane
by
4.3k points

2 Answers

1 vote

Answer :


\tt \Bigg[(2)/(3) + (1)/(6)\Bigg]


\tt = \Bigg[(2 * 2)/(3 * 2)+ (1)/(6)\Bigg]


\tt = \Bigg[(4)/(6) + (1)/(6)\Bigg]


\tt = \Bigg[(4 + 1)/(6)\Bigg]


\tt = (5)/(6)


\pink{\tt \therefore \: answer \: is \: (5)/(6)}

User Marc Hauptmann
by
5.2k points
4 votes

Answer:


→((2)/(3) + (1)/(6) ) \\ = ( (4)/(6) + (1)/(6) ) \\ = ((4 + 1))/(6) \\ = (5)/(6)

5/6 is the right answer.

User Gpcola
by
5.6k points